Transfer of Land Relations With Spatial Plan in The District of Pati - Ardika Budi Kusuma; Amin Purnawan (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
In this study, using the empirical jurisdiction, this research includes the identification law (common law) and research on the effectiveness of the law. Specifications of this research is descriptive, meaning from the results of this study will be described on the ruling, the legal system and analysis. Descriptive analytical research intended to describe of land rights transitional relationship with the spatial plan in Pati regency. The population in this research that all applicants for the use of a plot of land for specific uses in the district of Pati, while the sample is a subset or part of the population. The data used in this study are primary and secondary data. The data analysis used in this study is a qualitative analysis. The results of this research that the transfer of rights over land generally has nothing to do with the spatial plan, but related to the filing of the lands to be used as an industrial area, it needs to be made a rule of law or regulation that specifically applies to request transfer of rights over land will be used as an industrial area in Pati. During these provisions separately, as it is known that the transfer of land rights regulated in Act No. 5 of 1960 on Agrarian and Government Regulation No. 24 of 1997 on land Registration, which for the process require a long time with laws and regulations into one, then the parties will be easier to supervise and control the activities.Keywords: Transfer of Land; Spatial Planning; Pati.